Are 'intrinsic inflation persistence' models structural in the sense of Lucas (1976)? - Luca Benati (European Central Bank (ECB), 2009)
Following Fuhrer and Moore (1995), several authors have proposed alternative mechanisms to `hardwire' inflation persistence into macroeconomic models, thus making it structural in the sense of Lucas (1976). Drawing on the experience of the European Monetary Union, of inflation-targeting countries, and of the new Swiss monetary policy regime, I show that, in the Phillips curve models proposed by Fuhrer and Moore (1995), Gali and Gertler (1999), Blanchard and Gali (2007), and Sheedy (2007), the parameters encoding the `intrinsic' component of inflation persistence are not invariant across monetary policy regimes, and under the more recent, stable regimes they are often estimated to be (close to) zero. In line with Cogley and Sbordone(2008), I explore the possibility that the intrinsic component of persistence many researchers have estimated in U.S. post-WWII inflation may result from failure to control for shifts in trend inflation. Evidence from the Euro area, Switzerland, and five inflation-targeting countries is compatible with such hypothesis.
Keywords: E30; E32; 330; Bayesian estimation; Inflation persistence; New Keynesian models; Inflation; New-Keynesian Phillips Curve; Bayes-Statistik; Inflationssteuerung; Eurozone; Schweiz